SOSIALISASI HIDROPONIK SEBAGAI BASIS PENINGKATAN MASYARAKAT MERUPAKAN PENDONGKRAK NILAI TAMBAH KUALITAS PANGAN DI KELURAHAN GALANG KOTA - Jerniati Fahma; Yuniar Aprianti; Sri Fitria Jayusman (Jurnal Masyarakat Indonesia (Jumas), 2022)
This community service activity aims to further promote hydroponic plant activities, especially in urban areas, such as Galang Kota Village. Hydroponic cultivation is very suitable to be applied in urban areas that are already dense with settlements and buildings. Limited agricultural land, making people have to look for food supplies from outside the city. As a general description, Galang Kota Village has an area of ​​± 166.62 which has the potential for farming, but hydroponic farming is still rarely found. This of course can be an attractive business opportunity and can increase family income. Hydroponics can also create a beautiful and green environment, while still maintaining a clean and healthy environment.